The Use Of K-W-L (Know-Want-Learn) Strategy to Improve Students’ Reading Skill in Descriptive Text for the Eighth Grade Students of SMPN 1 Pecangaan Jepara in Academic Year of 2017/2018 - Indah Kusumaningrum; Muhammad Wahyu Widiyanto (ETERNAL (English Teaching Journal), 2018)
The objectives of the research are: (1) to find out the students’ reading skill taught by using K-W-L strategy, (2).to find out the students’ reading skill taught without by using K-W-L strategy, (3) to find out the significant difference on the students’ reading skill taught by using K-W-L strategy and taught without by using K-W-L strategy. This type of the research was quantitative research. The research design applied by the researcher was quasi experimental. The population of this research was all of eighth grade students in SMP N 1 Pecangaan Jepara in the academic year 2017/2018. The samples of this study were class VIIIAconsists 32 students and VIIIB consists 32 students. The instrument used to collect the data was a test that contents 30 multiple choice test. All of students are given pre-test and post-test for each group. The result of this research shows that (1) the students’ reading skill taught by using K-W-L strategy in criteria as good. It shown by the mean of post-test was 86.22, (2) the students’ reading skill taught without by using K-W-L strategy in criteria as adequate. It shown by the mean of post-test was 75.91, and (3) thus, the difference between the students’ reading skill taught with and without using K-W-L strategy was significant. It can be seen in the result t-test score was 8.73 with t-table significance 5% it was 1.67.The result of the t-test was higher than t-table. So, there is a significant difference between improving students’ reading skill taught with and taught without by using K-W-L strategy. It means that the students taught by using K-W-L strategy were better than the students taught without by using K-W-L strategy. From the research above, the researcher suggests that to improve the students’ reading skill by using K-W-L strategy, the students have to read a lot of reading texts, and try to comprehend the text. For the teacher, it would be better if the teacher can apply the strategies of teaching reading, especially for reading skill as a facilitator, motivator, and administrator.